Behavior Driven Energy Efficiency: A Customized Feedback Approach. (November 2015) - Shen, Meng; Cui, Qingbin
Abstract: Residential and commercial buildings consume 66% of the electricity and 33% of all energy in the United States and are therefore considered as a key sector to review for energy savings. Early studies have reported a great potential for achieving cost-effective energy efficiency in buildings through influencing behavioral change. However, it still remains a serious challenge to avoid negative boomerang effects in consumer behavioral change. Likewise, it is unclear how the lacking factor of the personality trait, which is vital to the success of normative feedback approach, shapes energy-related behaviors. To address these challenges, this paper presents a model-based approach to simulate the process of energy behavior change. Based on a modified opinion dynamics model, this study 1) explains the personality-behavior relations and acquires the elementary rules of behavior change by testing different treatment strategies; and 2) develops a personality trait-based energy reporting mechanism to lead behaviors towards more a favorable and sustained energy conservation movement.